New Energy Electric Vehicle Wireless Charging Technology - Zhu, Jiye (International Journal of Mechanical and Electrical Engineering, 2024)
With the global attention to renewable energy and environmental protection, new energy Electric Vehicles (EVs), as a green travel mode, are gradually becoming the development trend of the future automotive industry. However, problems such as inadequate charging infrastructure and long charging times limit the popularity of electric vehicles. The emergence of wireless charging technology provides a new way to solve these problems. This paper aims to discuss the principle, application status, advantages, challenges and future development trend of wireless charging technology for new energy electric vehicles.